Literature Review: Lingkungan Sosial dan Perilaku merokok pada Remaja - Devy Riyanti Adii Wijaya; Maya Icha Gayatri; Lina Handayani (Jurnal Cakrawala Promkes, 2022)
Smoking behavior is a problem related to public health conditions because it can lead to various health problems. A Global Youth Tobacco study in 2008 showed that the prevalence rate of adolescent smokers in Indonesia was very alarming. This study aims to determine a relationship between the social environment and smoking behavior in adolescents. The research method uses scientific research literature review, by analyzing various articles which valid and relevant to the topic. This study uses the literature of the National Journal published from 2018 to 2021. The database used to collect literature is Google Scholar with the keywords "Social Environment", "Smoking Behavior", "Adolescents". Researchers found 1,030 articles on Google Scholar then finally researchers got 10 articles relevant to the inclusion criteria. The results showed that from the ten articles, it was stated that the social environment and smoking behavior in adolescents were two interrelated things. The social environment is one ofthe driving factors for adolescents to smoke. The most influential adolescent social environment is family or parents and peers. Special assistance to adolescents is needed in order to reduce the prevalence of smoking in adolescents, especially in Indonesia.